Analisis Yuridis Putusan Bebas Pelaku Penadahan Cula Badak Jawa di Taman Nasional Ujung Kulon (Studi Putusan Nomor 93/Pid.Sus-LH/2024/PN Pdl) - Silvi Filya Sava (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines the acquittal decision in Case Number 93/Pid.Sus-LH/2024/PN Pdl concerning the alleged possession of Javan rhino horn, a species protected under Indonesian law. Despite the presence of electronic evidence, the court ruled that the criminal elements were not proven beyond reasonable doubt. Juridical analysis shows that the legal framework, particularly Undang-Undang Nomor 5 Tahun 1990, is normatively strong but weak in implementation. The decision reflects a gap between ecological justice and formal legal interpretation. Strengthening judicial capacity and integrating ecological perspectives are essential to ensure optimal protection of endangered species.